The Need for Laparoscopic Ovarian Transposition in Young Patients with Cervical Cancer Undergoing Radiotherapy - Winarto, Hariyono; Febia, Eva; Purwoto, Gatot; Nuranna, Laila (International Journal of Reproductive Medicine, 2013)
Maintaining the quality of life by preserving ovarian function in premenopausal patients with cervical cancer undergoing radiation is crucial. This can be accomplished with a simple and safe laparoscopic ovarian transposition procedure. This procedure aims to move the ovary out of the irradiation field, protecting it from direct radiation and irreversible damage and preserving its function. However, this procedure is often forgotten and seldom offered to patients. This review aims to lay stress on and reconsider the importance of laparoscopic ovarian transposition as a simple, safe, and extremely useful procedure. The biological effects of radiation are described briefly and several studies are evaluated, which reveal that this procedure has more benefits than risks.